A new conceptual model of experiences of aging in place in the United States: Results of a systematic review and meta-ethnography of qualitative studies. (March 2020) - Rosenwohl-Mack, Amy; Schumacher, Karen; Fang, Min-Lin; Fukuoka, Yoshimi
Abstract: Objectives: The purpose of this systematic review was to synthesize the evidence on experiences of aging in place in the United States. Design: Systematic review and meta-ethnography of qualitative studies. Data sources: We searched six bibliographic databases (PubMed, Embase, PsycINFO, CINAHL, Web of Science, Sociological Abstracts), with no limits on publication date. Eligible studies reported peer-reviewed qualitative research on experiences of aging in place in the United States with full-text available in English. Review methods: Three reviewers independently used Covidence software to screen titles and abstracts followed by full texts. We assessed quality and risk of bias using a modified version of the Joanna Briggs Institute Checklist for Qualitative Research. Qualitative data analysis was conducted using meta-ethnography, following Noblit and Hare's seven-step method of translation and synthesis to generate a novel conceptual model. Results: Of 2659 papers screened, 37 unique studies were eligible for inclusion, reported in 38 publications. The studies were conducted in 16 states and published between 1994 and 2018. The included samples represented 1199 participants in total, with mean ages ranging from 48 to 91 years. The gender of the samples ranged from 20% to 100% female, with a median of 77%. One-third of the included studies did not report participants' race/ethnicity, and half of the remaining study samples were at least 90% white; however, 20% of the studies focused exclusively on experiences of racial/ethnic minority older adults. Using meta-ethnography, we developed a new conceptual model of aging in place in the United States as a dynamic process of balancing threats and agency in relation to experiences of identity, connectedness, and place. We found that people aging in place were engaged in significant work to cope with unpredictable needs and challenges by changing their mindset, adapting their home environment to accommodate new needs, and finding different ways to connect with important people in their lives. Agency was shaped by resources and restrictions on choice, and where threats to aging in place outweighed an individual's sense of agency, the consequences included feelings of uncertainty, isolation, and dislocation. Conclusions: To the best of our knowledge, this is the first systematic review of qualitative studies to evaluate experiences of aging in place in the United States. The findings of our meta-ethnographic synthesis led to the development of a new conceptual model of aging in place highlighting the dynamic tensions involved in balancing threats and agency.